2011
DOI: 10.5897/ajbm11.468
|View full text |Cite
|
Sign up to set email alerts
|

Ownership structure and dividend policy: Evidence from Iran

Abstract: Ownership structure is an influential factor on firm policies. One of these policies is dividend policy. Therefore, a significant relationship between ownership structure and dividend policy is expected. This paper examined the relationship between dividend policy and ownership structure in Tehran Stock Exchange from 2000 to 2007. In this study, four regression models were used. Institutional ownership was negatively associated with dividend payout. It indicated that the presence of institutional investors res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 38 publications
2
16
0
Order By: Relevance
“…Jensen (1993) shows that the association between managerial ownership and dividend policy has been reported with a negative effect, i.e where the managerial ownership increase dividend policy pay will decrease. Mehrani et al (2011) find a negative association between managerial ownership and dividend pay-out policy which in support of the Chen, Cheng and Hwang ( 2005) and Short et al (2002) whom indicated a negative association between managerial ownership and dividend payment policy of bank holding company. Similarly, Chen, Cheung, Stouraitis and Wong (2005) reported a negative association between managerial ownership and firm performance.…”
Section: Managerial Ownership and Dividend Policysupporting
confidence: 54%
See 2 more Smart Citations
“…Jensen (1993) shows that the association between managerial ownership and dividend policy has been reported with a negative effect, i.e where the managerial ownership increase dividend policy pay will decrease. Mehrani et al (2011) find a negative association between managerial ownership and dividend pay-out policy which in support of the Chen, Cheng and Hwang ( 2005) and Short et al (2002) whom indicated a negative association between managerial ownership and dividend payment policy of bank holding company. Similarly, Chen, Cheung, Stouraitis and Wong (2005) reported a negative association between managerial ownership and firm performance.…”
Section: Managerial Ownership and Dividend Policysupporting
confidence: 54%
“…This result is in line with Fama and French (2000); Han et al (1999) and Short et al (2002) who reported that there is significant and positive association between the dividend policy and institutional ownership. While it contravenes the result of Mehrani et al (2011) who found negative relationship between dividend payment policy and institutional shareholders.…”
Section: Resultsmentioning
confidence: 50%
See 1 more Smart Citation
“…This is consistent with the works of Short, Zhang, and Keasey (2002) and Jayesh (2003). Mehrani, Moradi, and Eskandar (2011) found evidence of a negative relation between directive ownership and the dividend payment policy. Khan (2006) also analyzes the relation between dividends and ownership structure, arguing that there is a negative relation between the payment of dividends and the concentration of ownership; furthermore, the author finds that the composition of ownership is also a relevant variable.…”
Section: Review Of the Literaturementioning
confidence: 98%
“…Besides, there is also evidence that poor corporate governance has adverse effects on the group of minority shareholders. Mehrani et al (2011), examined the influence of the shareholders groups on the dividend policy of companies listed on the Tehran Stock Exchange of Iran. The findings demonstrate a positive influence on dividend payments if the stake of shareholders is highly concentrated.…”
Section: Theoretical Background and Related Literaturementioning
confidence: 99%